Musculoskeletal Disorders and Health Profile of Continuing Care Aides: An Urban-Rural Comparison. (August 2016) - Johnson, Shanthi; McLeod, Katherine; Engel, Patricia; Tulloch, Lori
The aim was to determine the prevalence of work-related musculoskeletal disorders (WMSDs) and health profile among urban versus rural continuing care aides (CCAs) in Canada. This cross-sectional study of 42 urban and rural CCAs assessed WMSDs and health profiles using the Nordic Musculoskeletal Questionnaire (NMQ), Cornell Musculoskeletal Discomfort Questionnaire (CMDQ), and a health background questionnaire. CCAs were generally unhealthy, with rural CCAs somewhat healthier. Greatest WMSD complaint was reported at the neck. Urban CCAs were more likely to report foot complaints ( p < .05). No other statistically significant differences were found. Back and shoulder scores were correlated with poorer nutrition status, higher body mass index, and more years worked. Workplace wellness programs should address the health issues faced by CCAs through active surveillance and practical interventions to improve CCAs' health status, prevent and manage WMSDs, and lost workdays.